PET radioligand binding to translocator protein (TSPO) is increased in unmedicated depressed subjects - Richards, Erica M.; Zanotti-Fregonara, Paolo; Fujita, Masahiro; Newman, Laura; Farmer, Cristan; Ballard, Elizabeth D.; Machado-Vieira, Rodrigo; Yuan, Peixiong; Niciu, Mark J.; Lyoo, Chul Hyoung; Henter, Ioline D.; Salvadore, Giacomo; et al. (EJNMMI research, 2018)
Background Inflammation is associated with major depressive disorder (MDD). Translocator protein 18 kDa (TSPO), a putative biomarker of neuroinflammation, is quantified using positron emission tomography (PET) and 11 C-PBR28, a TSPO tracer. We sought to (1) investigate TSPO binding in MDD subjects currently experiencing a major depressive episode, (2) investigate the effects of antidepressants on TSPO binding, and (3) determine the relationship of peripheral and central inflammatory markers to cerebral TSPO binding. Twenty-eight depressed MDD subjects (unmedicated ( n = 12) or medicated ( n = 16)) and 20 healthy controls (HC) underwent PET imaging using 11 C-PBR28. Total distribution volume ( V T , proportional to Bmax/Kd) was measured and corrected with the free fraction in plasma ( fp ). The subgenual prefrontal cortex (sgPFC) and anterior cingulate cortex (ACC) were the primary regions of interest. Peripheral blood samples and cerebrospinal fluid were analyzed to investigate the relationship between TSPO binding and peripheral and central inflammatory markers, including interleukins and neurotrophic factors previously linked to depression. Results TSPO binding was higher in MDD versus HC in the sgPFC (Cohen’s d = 0.64, p = .038, 95% CI 0.04–1.24) and ACC ( d = 0.60, p = .049, 95% CI 0.001–1.21), though these comparisons missed the corrected threshold for statistical significance ( α = .025). Exploratory analyses demonstrated that unmedicated MDD subjects had the highest level of TSPO binding, followed by medicated MDD subjects, who did not differ from HC. TSPO binding correlated with interleukin-5 in cerebrospinal fluid but with no other central inflammatory markers. Conclusions This study found a trend towards increased TSPO binding in the brains of MDD subjects, and post hoc analysis extended these findings by demonstrating that this abnormality is significant in unmedicated (but not medicated) MDD subjects.